Pendampingan Pengelolaan Keuangan Syariah untuk UMKM Berbasis Ekonomi Kreatif - Nurul Aisah; Ilham Karin Rizkiawan; Farid Muhammad Rofifudin; Nur Rahmawati (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
Creative economy-based MSMEs contribute greatly to opening up employment opportunities and improving community welfare. However, the sustainability of MSME businesses is often hampered by weak financial management, especially those based on sharia principles, including MSME D & R SNACK. The main problem faced by partners, namely MSME D & R SNACK, is low financial literacy, especially sharia principles and lack of ability to record and analyze cash flow, making it difficult to evaluate the business. The purpose of this community service is to increase knowledge of sharia finance and improve cash flow recording and analysis skills to conduct business evaluations. The Transfer Knowledge service method uses several stages of activities that will be implemented, including socialization, training, mentoring, and ongoing activities that will be implemented starting from January-March 2025. The results of this service are that partners experience an increase in knowledge and skills from 29% to 100% of participants who have stated that they know sharia finance and cash flow recording. Sharia finance helps MSMEs manage finances ethically, fairly, and blessedly.